1997
DOI: 10.1023/a:1007402505482
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The first technique for large-scale preparation of isolated hepatocytes was described in 1953 and involved perfusion of rat liver under pressure with a Ca(2+)-free solution containing a chelating agent. Various modifications of this technique were in use over the next ten years, until it was demonstrated that cells prepared in this manner were grossly damaged, losing most of their cytoplasmic enzymes during the preparative procedure. The successful preparation of intact isolated hepatocytes by collagenase-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Hepatocyte Isolation and Culture-Mouse hepatocytes were isolated by a modified two-step perfusion procedure (37,38). In brief, mice were perfused retrograde through the hepatic vein via the inferior vena cava and out the severed portal vein, with the inferior vena cava clamped above the diaphragm.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocyte Isolation and Culture-Mouse hepatocytes were isolated by a modified two-step perfusion procedure (37,38). In brief, mice were perfused retrograde through the hepatic vein via the inferior vena cava and out the severed portal vein, with the inferior vena cava clamped above the diaphragm.…”
Section: Methodsmentioning
confidence: 99%
“…In the first step, the perfusion of the liver piece with the EGTA-containing perfusion solution causes a depletion of Ca 2+ within the tissue. As a consequence, the desmosomes, which are responsible for cell–cell connections, undergo structural changes that cause a weakening or an irreversible complete loss of cell–cell linkages, so that the desmosomes are unable to reform even when the tissue is perfused with a second perfusion solution containing high concentrations of Ca 2+ , which is needed for the collagenase activity (Berry et al 1997). During step 2 of the perfusion process, cell–matrix contacts are destroyed by the digestion of ECM proteins with collagenase.…”
Section: Liver In Vitro Models In Pharmacology Toxicology and Basic mentioning
confidence: 99%
“…Low collagenase activity and high protease/trypsin activity correlate with a decrease in isolation efficiency with regard to cell yield and cell viability (Berry et al 1997). In general, but not invariably, the most rapid digestions and the best yields of intact cells are achieved with preparations of highly active collagenase (Berry et al 1997).…”
Section: Liver In Vitro Models In Pharmacology Toxicology and Basic mentioning
confidence: 99%
“…Several studies have indicated that the glycolytic and gluconeogenic enzymes present in the cell are associated in the form of multienzyme complexes [56,57]. PC is also found to be specifically associated with other mitochondrial enzymes : in binary complexes with mitochondrial aspartate transferase or malate dehydrogenase, in a ternary complex with aspartate aminotransferase and glutamate dehydrogenase, and in a quaternary complex with aspartate aminotransferase, glutamate dehydrogenase and malate dehydrogenase [58].…”
Section: Synthesis Degradation and Intracellular Localization Of Pcmentioning
confidence: 99%